Hematological recovery in male ultramarathon runners: the effect of variations in training load and running time - Peters, E. M.; Robson, P. J.; Kleinveldt, N. C.; Naicker, V. L.; Jogessar, V. D. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: Haematological response to the 2001 downhill Comrades Marathon was compared in high (>120 km/w in training; 3 weeks of pre-race taper) and low (<80 km/w in training; 2 weeks of pre-race taper) training status groups. METHODS: Full blood counts, differential lymphocyte counts (CD3, CD4, CD8, CD19, CD56), serum cortisol, C-reactive protein (CRP) and creatine kinase (CK) were measured in blood samples donated 21 hours before and 16 hours after a 90 km ultramarathon. RESULTS: Despite significantly faster mean race finishing time (8.03 h vs 10.53 h; p<0.001) and greater percentage incidence (55.6 % vs 40 %) of post-race upper respiratory tract infection (URTI) in the highly trained group, these faster runners did not show evidence of a slower post-race recovery in terms of total leukocyte, neutrophil, total or differential lymphocyte counts (p>0.05). CRP concentrations were, however, markedly higher in the slower, less trained group (65.3+/-10.7 vs 38.3+/-5.9; p<0.01). CONCLUSIONS: Despite greater systemic evidence of post-race muscle inflammation and an acute phase response in the slower runners in a downhill ultramarathon race, the haematological recovery of well trained runners who undergo a 3-week taper period prior to the ultramarathon is not different to that in less trained runners who spend almost 3 hours longer on the road. The higher prevalence of post-race URTI symptoms in the fast, well trained group does not appear to be related to lymphocyte recovery in peripheral blood.